BEHBUDIYA AND THE IMPORTANCE OF “NASHRIYOTI BEHBUDIYA” IN YOUTH EDUCATION - Mirzoyeva Nigora Shavkatjonovna; Hakimova Marjona Iskandarzoda (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this article, it is considered that Mahmudhoja Behbudi is a great representative of the jadidist movement, the leader of the country’s jadidists, that Behbudi was effective in pedagogy, journalism, journalism, publishing, politics, commerce and a number of other activities. Behbudi’s contribution to the formation and development of new Uzbek literature and the activities of the enlightener, modern schools, “Behbudiya library”, “Behbudiya Publishing House” and a number of other issues are also presented.